Divided lives : - Crance, Cynthia (Palgrave Macmillan, 2003)
"Mischlinge" was the term given by Hitler to Germans who had some Jewish background. A number of these folks were able to precariously steer their way through the Nazi years without becoming a victim of the death camps. After explaining the laws that affected these people, Crane (English, U. of Cincinnati) interviews 11 women who were in this situation and presents their stories.